Efeito da temperatura sobre a degradação de força e resistência à corrosão in vitro de molas fechadas de NiTi - Pompeo, Daniela Daufenback (2016)
The coil springs NiTi exhibit excellent elastic properties, which gives them the ability to exert constant forces during its deformation over a long period. However, when being subjected to additional processes in their manufacture, can undergo changes in their mechanical properties, including force degradation under significant temperature variations. This in vitro study aims to evaluate the force degradation of closed coil springs NiTi subjected to constant force under different temperature conditions. A total of 270 closed coil springs, 135 of Morelli® and 135 of RMOTM and subjected to constant forces on standardized jigs of polyvinyl chloride tubes, separated horizontally by 5 mm distance and distended 21mm. The specimens were immersed in artificial saliva, distributed in bottles with 3 different temperatures (15ºC, 37ºC and 55ºC) controlled by a thermostat and digital thermometer. The force was measured by means of a digital dynamometer during the experimental period by a blinded investigator, in the following intervals: baseline (0), 1, 7, 14, 21 and 28 days. During each interval period will be selected 6 coil springs (3 of each brand) for corrosion analysis. Open Circuit Potential was realized with the aid of electrochemical cells composed of two electrodes. For corrosion testing, artificial saliva will be used as electrolyte at room temperature in a Potentiostat / Galvanostat. The potentiodynamic curves will be examined by Voltamaster 4 software. The average force of RMOTM springs, in three temperatures analyzed was statistically higher at baseline than NiTi springs Morelli®. During the periods occurred oscillation of the middle forces in both brands, and at the end of 28 days was no statistically significant difference between them at different temperatures. The corrosion resistance was different in the brands analyzed, but both are influenced by temperature. From the results, it can be concluded that the variation in temperature did not affect the strength degradation of NiTi springs, however the temperature of 55o C decreased corrosion resistance